PELATIHAN KOMPUTER AKUNTANSI BAGI GURU MGMP EKONOMI/AKUNTANSI KEMENAG KOTA BANJARMASIN - Nurul Qalbiah; Putriana Salman; Rusman Irwansyah (LPPM Universitas Bina Bangsa, 2023)
The rapid development of technology has an impact on the education sector. Schools are required to produce graduates who are aware of technology in order to get jobs quickly. One of the technologies often used by companies is application-based financial reporting, for example. the Zahir Accounting application. Teachers who are members of the Musyawarah Guru Mata Pelajaran (MGMP) Economics/Accounting the Ministry of Religion of the Banjarmasin City have only provided manual financial reporting knowledge to their students, so there has been no accounting learning combined with accounting applications. The purpose of implementing this activity is to provide knowledge and skills for MGMP Economics/Accounting teachers in computerized financial reporting. The method used are the lecturer method, the simulation method, and the practice method and discussion. The result of this activity is that teachers gain knowledge and skills in using accounting applications, then these teachers can transfer the knowledge gained to their students